Natural and man-made health hazards in rural Slovakia - Gulis, Gabriel; Kollarová, Jana; Dietzová, Zuzana; Labancová, Jana; Behanová, M; Ondrušová, Martina (Central European Journal of Public Health, 2009)
Context: There is little information on health situation of the people of rural Slovak Republic. The rural environment is often a mixture of natural and man-made hazards, which under some conditions, might turn to be a health risk to humans. Purpose: The aim of this study was to compare two regions of the Slovak Republic, two different hazards (natural and man-made), two different methods of health outcome measurement (routine statistics and individual diary based data). Methods: Ecological study design with focus on cancer incidence analysis was employed in case of natural hazard analysis. Standardized incidence ratios (SIR) were calculated and are presented in paper. Observational study design was employed to study rural gardening practices and their impact on health. Findings: Statistically significant differences in SIR were found in rural areas of Spis-Gemer Region (SGR) among males for lip, oral cavity and larynx (1.60, CI 95% 1.12–2.34), respiratory (1.25, CI 95% 1.01–1.55) and digestive organ cancers (1.22, CI 95% 1.01–1.47); hematopoetic cancers are significantly elevated among males in rural areas as well (1.58, CI 95% 1.05–2.39). Pesticide use (83.1% of gardeners use pesticides) without any protective equipment is still widespread among gardeners in rural Slovak Republic (16.9%). The produced fruits and vegetables are substantial part of total fruit and vegetable consumption (51% in summer and 42.7% in winter season) increasing the risk of exposure to pesticides. Conclusion: Our study shows that on ecological level, mortality and morbidity statistics could be used to assess human health status in linkage to broad exposure measures (urban- rural); on dose response level (arsenic in soil) this method lacks sensitivity. Health survey and diary method on the other hand are useful tools in analysis of rural health especially with respect to man-made hazards.
Keywords: financování organizované; Statistics as Topic; agrochemikálie; statistika jako téma; Vital Statistics; zahradničení; Neoplasms; nádory; Hazardous Substances; Slovakia; znečištění životního prostředí; lidé; arsen; Environmental Pollution; Agrochemicals; Financing, Organized; zdraví venkovských oblastí; Pesticide Residues; Epidemiologic Studies; statistika přirozeného pohybu; rezidua pesticidů; Gardening; Arsenic; Rural Health; Slovenská republika; epidemiologické studie; nebezpečné látky; Humans